Biomarkers for the clinical development of antiviral therapies. Issue 1 (8th December 2020) - Ng, Teresa I.; Dorr, Patrick K.; Krishnan, Preethi; Cohen, Daniel E.; Rhee, Susan; Wang, Stanley X.; Ruzek, Melanie C.; Mensa, Federico J.; Kati, Warren M.
Abstract: With the morbidity and mortality associated with the COVID‐19 pandemic that we are witnessing this year, the risks posed by emerging viral diseases to global health are all too obvious. This pandemic highlights the importance of antiviral drug discovery, which targets emerging viral pathogens, as well as existing pathogenic viruses that undergo continuous evolution. Drug discovery and development is a long and resource intensive process; however, the use of biomarkers can accelerate clinical development of antivirals by providing information regarding diagnosis of specific viral infections, status of infection, potential safety parameters, and antiviral responses. In clinical practice, many of the biomarkers initially utilized to support clinical development are also used for patient care. While viral load is a standard and essential biomarker used to detect the desired viral suppression induced by an antiviral agent, it has become apparent that additional biomarkers, whether related to the virus, the host or as a consequence of the drug's mechanistic effects, are also important for monitoring clinical outcomes associated with an antiviral therapy. This review summarizes the biomarkers used in the clinical development (as well as in clinical practice, where appropriate) of antiviral therapies for hepatitis C virus, hepatitis B virus, human immunodeficiency virus, and severe acute respiratory syndrome coronavirus 2.